2018
DOI: 10.1111/are.13899
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an insulin‐like androgenic gland hormone transcript highly expressed in male precociousness of the Chinese mitten crab Eriocheir sinensis

Abstract: The androgenic gland (AG) hormone is well known as a key peptide to induce masculinization and maintains male characteristic in crustaceans. In this study, a fulllength cDNA encoding insulin-like androgenic gland hormone (EsIAG) was identified from the AG of the Chinese mitten crab Eriocheir sinensis. The full length of EsIAG cDNA contains 1,481 nucleotides, which encodes for a deduced protein of 151 amino acid residues. The predicted pre-peptide is composed of a signal peptide of 19 amino acids (aa), A chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Dsx is responsible for male sex determination/differentiation in Drosophila (Verhulst & van de Zande, 2015). IAG is an insulin‐like androgenic gland hormone gene, which has been well characterized as a switch gene for male sexual development in crustaceans (Liu, Ma, & Qiu, 2019; Ventura et al, 2009). Given that many miRNA candidates were deduced to target the crab IAG and Dsx (Table 1), we selected miRNAs to verify their direct interaction with IAG and Dsx by dual‐luciferase reporter assay (Figures 5 and 6).…”
Section: Discussionmentioning
confidence: 99%
“…Dsx is responsible for male sex determination/differentiation in Drosophila (Verhulst & van de Zande, 2015). IAG is an insulin‐like androgenic gland hormone gene, which has been well characterized as a switch gene for male sexual development in crustaceans (Liu, Ma, & Qiu, 2019; Ventura et al, 2009). Given that many miRNA candidates were deduced to target the crab IAG and Dsx (Table 1), we selected miRNAs to verify their direct interaction with IAG and Dsx by dual‐luciferase reporter assay (Figures 5 and 6).…”
Section: Discussionmentioning
confidence: 99%
“…The spermatids in the most spermatogenic acinus of IAG‐treated crayfish were already at stage Ⅳ, which could be observed in visible spines, indicating that the testes in the experimental group developed faster than those in the control group. The IAG was found to be expressed at higher levels in precocious Eriocheir sinensis than in normal grown individuals indicated that IAG played a vital function in maintaining male characteristics (Liu et al, 2019). It indicated that the IAG recombinant protein could promote the testicular development.…”
Section: Discussionmentioning
confidence: 99%
“… 10 This observation could explain why AG manipulation led to complete sex change in M. rosenbergii and could perhaps explain why it failed in other species. In Jonah crab ( Cancer borealis ), tiger shrimp ( Penaeus monodon ), eastern spiny lobster ( Sagmariasus verreauxi ), southern spiny lobster ( Jasus edwardsii ), redclaw crayfish ( C. quadricarinatus ), African freshwater prawn ( Macrobrachium vollenhovenii ) and Chinese mitten crab ( Eriocheir sinensis ), the only tissue expressing iag is the AG (Table 1), 11,14,17,44–47 and therefore, silencing iag may prove successful in inducing sex change in these decapod species. Given that successful sex change was not achieved to date in any decapod species other than M. rosenbergii , more aspects should be considered, as detailed below.…”
Section: The Key Aspects To Considermentioning
confidence: 99%
“…African freshwater prawn (Macrobrachium vollenhovenii) and Chinese mitten crab (Eriocheir sinensis), the only tissue expressing iag is the AG (Table 1), 11,14,17,[44][45][46][47] and therefore, silencing iag may prove successful in inducing sex change in these decapod species. Given that successful sex change was not achieved to date in any decapod species other than M. rosenbergii, more aspects should be considered, as detailed below.…”
Section: Is Iag Expressed Explicitly In the Ag?mentioning
confidence: 99%